2019
DOI: 10.1001/jamaophthalmol.2018.5413
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blepharitis and Ectropion With Tumor Necrosis Factor α Inhibitor Treatment in Crohn Disease

Abstract: Role of the Funder/Sponsor: The funding organizations had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication. Additional Contributions:We thank the patient for granting permission to publish this information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Most cases consist of anterior uveitis (AU), although the induction of intermediate uveitis [29], posterior uveitis [30], scleritis [31], and even orbital myositis [32] has been reported. Other ocular adverse events include blepharitis and ectropion [33], optic neuritis [28], visual impairment [34], diplopia [34][35][36], endophthalmitis [37,38], and "sarcoid-like granulomatosis" [39], panuveitis [40], or retinal vasculitis [41].…”
Section: Ocular Adverse Eventsmentioning
confidence: 99%
“…Most cases consist of anterior uveitis (AU), although the induction of intermediate uveitis [29], posterior uveitis [30], scleritis [31], and even orbital myositis [32] has been reported. Other ocular adverse events include blepharitis and ectropion [33], optic neuritis [28], visual impairment [34], diplopia [34][35][36], endophthalmitis [37,38], and "sarcoid-like granulomatosis" [39], panuveitis [40], or retinal vasculitis [41].…”
Section: Ocular Adverse Eventsmentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNF-α) inhibitors are commonly used in the treatment of several autoimmune disorders such as rheumatoid arthritis, psoriasis, and Crohn's disease [28]. Although they are effective in controlling inflammation, TNF-α inhibitors have been associated with various ocular side effects, including blepharitis [29,30].…”
Section: Blepharitis and Tnf-α-inhibitorsmentioning
confidence: 99%
“…They both act by binding to TNF-α, thus inhibiting its action and reducing inflammation. The exact mechanism by which TNF-α inhibitors cause blepharitis remains unclear, but it has been suggested that it may be a paradoxical reaction thought to be secondary to genetic susceptibility, dominance of helper T cells types 1 and 17, and excessive immune response from interferon-α overproduction by plasmacytoid dendritic cells [29].…”
Section: Blepharitis and Tnf-α-inhibitorsmentioning
confidence: 99%

Uncommon Blepharitis

Di Zazzo,
Giannaccare,
Villani
et al. 2024
JCM
“…Meist handelt es sich dabei um eine Uveitis anterior (UA), doch wurde auch die Auslösung einer intermediären Uveitis [29], einer Uveitis posterior [30], einer Skleritis [31] und sogar einer orbitalen Myositis [32] berichtet. Andere okuläre Nebenwirkungen sind Blepharitis und Ektropium [33], Optikusneuritis [28], Verschlechterung des Sehvermögens [34], Diplopie [34-36], Endophthalmitis [37, 38] und «sarcoid-like granulomatosis» [39], Panuveitis [40] oder retinale Vaskulitis [41].…”
Section: Okuläre Nebenwirkungenunclassified